Three new trixane glycosides obtained from the leaves of Jungia sellowii Less. using centrifugal partition chromatography - Azevedo, Luíse (Beilstein J Org Chem, 2016)
Jungia sellowii (Asteraceae) is a shrub that grows in Southern Brazil and polar extract of its leaves presents anti-inflammatory properties. Cyperane, guaiane, nortrixane, and trixane sesquiterpene types were reported as the main metabolites in Jungia species. This work aims to describe the isolation and identification of sesquiterpenes in the leaves of J. sellowii using liquid–liquid partition and centrifugal partition chromatography. Thus, the crude extract of fresh leaves of J. sellowii was partitioned with hexane, dichloromethane, ethyl acetate and butanol, respectively. The butanol fraction was then subjected to a selected ternary system optimized for the CPC (centrifugal partition chromatography): ethyl acetate–ethanol–water (9:2:10, v/v/v). The separation was carried out isocratically at a flow rate of 25 mL/min at 1200 rpm, affording seven fractions A to G. TLC of fractions B, C and F displayed a single spot corresponding to three new glycosylated sesquiterpenoids. Their structures were established by using spectroscopic data in comparison to those reported in the literature. Furthermore, the isolates were evaluated for their leishmanicidal and cytotoxic effects. No cytotoxic effect was observed against the three cancer cell lines (HL60, JURKAT and REH), but compound 1 showed a weak antiprotozoal activity. Liquid–liquid partition and CPC turned to be a versatile technique of glycoside purification which is environmentally friendly and requires a limited amount of organic solvents.